Single-cell transcriptomic analysis reveals characteristic feature of macrophage reprogramming in liver Mallory-Denk bodies pathogenesis - Zixuan Fang; Bei Zhong; Yi Shi; Wanmei Zhou; Maoping Huang; Samuel W. French; Xiaoping Tang; Hui Liu (Journal of Translational Medicine)
Abstract Chronic liver diseases are highly linked with mitochondrial dysfunction and macrophage infiltration. Mallory-Denk bodies (MDBs) are protein aggregates associated with hepatic inflammation, and MDBs pathogenesis could be induced in mice by feeding 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC). Here, we investigate the macrophage heterogeneity and the role of macrophage during MDBs pathogenesis on DDC-induced MDBs mouse model by single-nucleus RNA sequencing (snRNA-seq). We defined liver macrophages into four distinct subsets including monocyte-derived macrophages (MDMs) subset and three Kupffer cells (KCs) subsets (Gpnmbhigh KCs, Peam1high KCs, and Gpnmblow Pecam1low KCs). Particularly, we identified a novel Gpnmbhigh KCs subset as lipid-associated macrophage (LAM) with high expression of Trem2, CD63, and CD9. Interestingly, LAM showed a potential immunosuppressive characteristic by expressing anti-inflammatory genes IL-7R during the MDBs formation. Using contact and transwell co-culture systems, the released mtDNA from hepatocytes was found to induce the activation of inflammasome in macrophages. Furthermore, we revealed the damaged DNA could activate the NOD-like receptor family pyrin domain containing-3 (NLRP3) inflammasome and subsequently form apoptosis-associated speck-like protein containing a caspase recruit domain (ASC) specks of liver macrophages. Collectively, our results firstly revealed macrophage heterogeneity and inflammasome activation by mtDNA from injured liver during MDBs pathogenesis, providing crucial understanding of pathogenesis of chronic liver disease.